5(x+2)=25x

Simple and best practice solution for 5(x+2)=25x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)=25x equation:


Simplifying
5(x + 2) = 25x

Reorder the terms:
5(2 + x) = 25x
(2 * 5 + x * 5) = 25x
(10 + 5x) = 25x

Solving
10 + 5x = 25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25x' to each side of the equation.
10 + 5x + -25x = 25x + -25x

Combine like terms: 5x + -25x = -20x
10 + -20x = 25x + -25x

Combine like terms: 25x + -25x = 0
10 + -20x = 0

Add '-10' to each side of the equation.
10 + -10 + -20x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -20x = 0 + -10
-20x = 0 + -10

Combine like terms: 0 + -10 = -10
-20x = -10

Divide each side by '-20'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 5m+8/7=4 | | 2.1n-5.31=18 | | 10x^2+7x= | | (3y^2+8y-4)-(-4y+2)= | | 9y-5=-14 | | 69*x=9000000000 | | -5=c/7 | | 3(2x+4)=6 | | (6x^2+8)-(3x^2-12)= | | 6x+3=23x | | -6x+2(5x+1)=6 | | (5x^2+8)-(11x^2-3)= | | (5x^2-2x-2)-(-3x^2-3x-8)= | | -6x-3(2x-2)=-6 | | 3y=9 | | (7t^3+2t)-(-7t^3-4t+5)= | | (7x+7)-(9x-6)= | | -3x-4(4x+11)=-5 | | -2(4+-11)=-18 | | -9r/4 | | 4x-6(2x+4)=-8 | | 9x-85+49/70=x | | -3(3t-7)=66 | | 4x+4(-3x-2)=8 | | y^2+8=12 | | 5x+11=-19 | | 5x+2=-53 | | 9(3G+6)=40.5 | | 5x+10=30findx | | 6(x+4)=3(x+16) | | 1/3(b+6)=1/4b | | 2377960+26d=3000000 |

Equations solver categories